Serum Lipid Profile in Sheep Fed Diet Incorporated with Feed Additives - Beigh, Yasir A; Ganai, Abdul M; Muzamil, Showkeen; Mir, Danish; Ahmad, Haidar A; Mir, Shahid H (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
A feeding trial to study the supplementation effect of exogenous fibrolytic enzymes (EFE) cocktail and wormwood herb on serum lipid profile was conducted for 90 days in twenty crossbred lambs that were divided into four equal groups viz. T0 (Control) and T1, T2 and T3 (treatment groups). T0 received total mixed diet (TMR) without any supplementation, while in treatments groups TMR was supplemented either with EFE cocktail alone @ 0.60% (T1) or wormwood herb alone @ 4.50% (T2) and in a combination of the two feed additives (T3). At the end of the feeding trial, 6 days of digestibility trial was carried out to assess the supplementation effect in vivo on nutritional parameters and serum total lipids and different lipoprotein fractions were carried out at the start (0 d) and subsequently at monthly intervals of the experiment (30, 60 and 90 d). Nutrient digestibility, content as well intake were significantly higher in groups fed diets supplemented with the feed additives either alone (p <0.05) or in-combination (p <0.01). No significant effect was observed on the total cholesterol level at any point of evaluation, and on total triglycerides level-up to 30 d, but significant reduction was noted in T2 at 60 (p <0.05) and 90 (p <0.01) days as compared to T1. Significant (p <0.01) effect on HDL level was evident as elevated in T2 while reduced in T1 at day 60 and 90. In contrast, LDL values were reduced in T2 and elevated in T1 group at day 30 (p <0.05), 60 and 90 (p <0.01). VLDL levels did not change among the groups up to 30 d, whereas reduced at day 60 (p <0.05) and 90 (p <0.01) in T2 as compared to T1. Lowest (p <0.01) AI value was observed in the T2 group at day 90 compared to other groups. It was concluded that dietary incorporation of wormwood herb as a feed additive for sheep improved nutritional status along with health beneficial effects when supplemented alone.